Latgale Seniors’ Satisfaction with Life as One of the Indicators of Quality of Life - Ušča, Svetlana; Ļubkina, Velta; Kaupužs, Aivars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Aging rates and pace of Latvia population are higher and more rapid, the number of people over the working age increases. In this context, such questions as how to prolong their economic and socially active life period appear. One of the solutions would be to create opportunities to increase seniors' satisfaction with life by improving the quality of life according to their needs. Objective of the paper is to study indicators of seniors' quality of life and analyze Latgale seniors' satisfaction with life. Latgale seniors' satisfaction with life is viewed taking into consideration the overall level of national wealth; results of the survey that was carried out within the framework of the project "Evaluation toolkit on seniors education to improve their quality of life" are analyzed.